EXPERT SYSTEM DETERMINES MENU NUTRITION FOR PREGNANT WOMEN - Saputri, Tri Aristi; Perdana, Andreas; Pusfitasari, Desi (International Research on Big-Data and Computer Technology: I-Robot, 2020)
In the process of pregnancy, food intake must be considered. Maintain nutritional balance during pregnancy, and it can be achieved by consuming a variety of foods every day. These diverse foods need to be prepared according to the energy needs of pregnant women. The lack of knowledge of pregnant women in determining food intake following daily energy needs requires that pregnant women are nutritionists or midwives in their area. This study aims to design and create an expert system that can provide food for pregnant women according to their daily calorie needs. The Harris-Benedict method calculates the caloric value based on height and weight, age of pregnant women, activity values, pregnancy. In making this expert system, the system development method is used in Object-Oriented Software Engineering (OOSE). The results of application testing use black-box testing with system functionality that runs well and provides calculations according to the manual process. The output of this system is the number of calorie needs of pregnant women and recommendations for food that should be consumed.